Effect of gastric fluid aspiration on the lung microbiota of laboratory rats. (28th May 2018) - Finn, Sade M. B.; Scheuermann, Uwe; Holzknecht, Zoie E.; Parker, William; Granek, Joshua A.; Lin, Shu S.; McKenney, Erin A.; Barbas, Andrew S.
Abstract: Aim of the Study: The pulmonary microbiota is important for both normal homeostasis and the progression of disease, and may be affected by aspiration of gastric fluid. The aim of this study was to investigate changes in the lung microbiota induced by aspiration of gastric fluid in a laboratory rat model. Material and Methods: Using the intratracheal application method, male rats received aspiration with 0.9% normal saline (n = 11); gastric fluid (n = 24) or sterilized (gamma-irradiated) gastric fluid (n = 12) once-weekly for four weeks. On the fifth week, the animals were sacrificed, and the microbiota of the lung was assessed by 16S ribosomal RNA gene sequencing. Results: Lungs without aspiration and lungs after aspiration with normal saline had similar microbial compositions, dominated by bacteria of the genera Serratia, Ralstonia and Brucella. Evaluation of the microbiota following aspiration of gastric fluid revealed a much different profile that was dominated by bacteria from the genera Romboutsia and Turicibacter and largely independent of sterilization of the gastric fluid. Conclusion: In a laboratory rat model, aspiration with gastric fluid caused a substantial shift of the lung microbiota that could be characterized as a shift from Proteobacteria towards Firmicutes, possibly of enteric origin. Bacteria contained in the gastric fluid are not apparently responsible for this change.